Molecular characterization of Colletotrichum species causing soybean anthracnose in Argentina - Ramos, A.M. (2013)
Twenty-six isolates obtained from soybean crops (Glycine max) with typical anthracnose symptoms were identified as Colletotrichum truncatum (73 %) and C. destructivum (26 %). Their genetic relationships were studied using the AFLP method. A UPGMA phenogram divided the strains into two clusters corresponding with the two species. Genetic distances based on association coefficient were 0.71-0.89 among the 18 C. truncatum strains and 0.67-1 among the eight C. destructivum strains. Genetic variability within species, measured in terms of percentage of polymorphic loci, was high (<90%). Only two isolates showed 100% similarity, suggesting high intraspecific variability. © 2013. Mycotaxon, Ltd.